Critical-thinking assessment table: a novel strategy to foster students’ critical thinking dispositions - Ahmad Sulaiman (Jurnal Ilmiah Psikologi Terapan, 2018)
Abstrak. Disposisi berfikir-kritis adalah aspek penting dalam diri siswa yang mendorong mereka untuk berfikir-kritis baik dalam kehidupan akademik dan sehari-hari. Sayangnya, para peneliti menaruh perhatian yang begitu kecil kepada disposisi berfikir kritis. Penelitian ini bertujuan untuk mengembangkan dan menguji coba suatu strategi baru untuk menumbuhkan disposisi berfikir-kritis tiga mahasiswa pascasarjana Indonesia. Strategi itu direpresentasikan dalam sebuah tabel yang berisi kriteria berfikir-kritis dan fase regulasi diri berfikir-kritis. Strategi tersebut bertujuan untuk menjadikan eksplisit sekaligus melatih metakognisi dan regulasi diri siswa dalam proses berfikir kritis. Nilai yang didapat dari skala disposisi berfikir-kritis menunjukkan bahwa intervensi berhasil meningkatkan disposisi berfikir kritis pada siswa. Sementara itu, interview mengungkap beberapa temuan yang berharga mengenai kesulitan pembelajaran siswa dan bagaimana intervensi telah berhasil membuat siswa menyadari proses berfikirnya disamping, melatih metakognisi dan regulasi diri mereka. Keterbatasan dan implikasi dari strategi ini akan didiskusikan lebih lanjut.Kata kunci: disposisi berfikir kritis, regulasi diri, metakognisiAbstract. Critical-thinking dispositions are integral to drive and maintain students’ use of critical-thinking in their academic and daily life setting. Yet, critical-thinking dispositions have received small attention from researchers. The present study developed and tested a novel strategy aimed to foster three Indonesian Master Students’ critical-thinking dispositions. The strategy represented by a table consisting of a set of critical-thinking criteria and phases of critical-thinking self-regulation. The strategy intended to make explicit and to enhance the students’ metacognition and self-regulation in the process of critical-thinking. Scores retrieved from critical-thinking dispositions scale shows that the intervention successfully increased the overall students’ level of critical-thinking dispositions. The qualitative data from individual interviews revealed some valuable insights about the students’ learning difficulties and that the strategy successfully made students aware of their thinking process and reinforced the students’ metacognition and self-regulation process. The limitation and implication of the strategy are discussed.Keywords: critical-thinking dispositions, self-regulation, metacognition